FACTORS AFFECTING MOTOR VEHICLE TAXPAYER COMPLIANCE (EMPIRICAL STUDY: TAXPAYERS TRANSACTING AT SAMSAT, SOUTH JAKARTA) - -, Masripah; Subagyo, Betty (Polytechnic of State Finance STAN, 2024)
This study aims to determine whether there is influence from quality of tax services, modernization of the tax administration system, tax socialization, and tax write-off amnesty on motor vehicle taxpayer compliance. This study uses a quantitative method with a sample of motorized vehicle taxpayers who are transacting at SAMSAT South Jakarta. The sampling technique used simple random sampling with a total sample of 151 respondents. The data is processed and tested using the SEM-PLS method with the SmartPLS 3.0 application. The results of this study indicate that the quality of tax services, modernization of the tax administration system, and tax socialization significantly influence motor vehicle taxpayer compliance. Meanwhile, tax write-off has no effect on motor vehicle taxpayer compliance. The limitation experienced in this research is that many taxpayers are not willing to fill out the published questionnaire. This research can contribute to motor vehicle taxpayers in order to increase taxpayer awareness and compliance with applicable laws and regulations, South Jakarta SAMSAT in order to put forward suggestions for improving services, so that every year services can continue to be improved and all taxpayers are increasingly aware of their responsibilities. as well as motor vehicle tax rights, and can provide additional references and new comparative material for future researchers with different methods and scope in the same field.